Phthalate exposure and female reproductive and developmental outcomes: a systematic review of the human epidemiological evidence - Elizabeth G. Radke; Barbara S. Glenn; Joseph M. Braun; Glinda S. Cooper (Environment International, 2019)
Objective: We performed a systematic review of the epidemiology literature to identify the female reproductive and developmental effects associated with phthalate exposure. Data sources and study eligibility criteria: Six phthalates were included in the review: di(2-ethylhexyl) phthalate (DEHP), diisononyl phthalate (DINP), dibutyl phthalate (DBP), diisobutyl phthalate (DIBP), butyl benzyl phthalate (BBP), and diethyl phthalate (DEP). The initial literature search (of PubMed, Web of Science, and Toxline) included all studies of female reproductive and developmental effects in humans, and outcomes were selected for full systematic review based on data availability. Study evaluation and synthesis methods: For each outcome, studies were evaluated using criteria defined a priori for risk of bias and sensitivity by two reviewers using a domain-based approach. Evidence was synthesized by outcome and phthalate and strength of evidence was summarized using a structured framework. Results: The primary outcomes reviewed here are (number of included/excluded studies in parentheses): pubertal development (5/13), time to pregnancy (3/4), preterm birth (8/12), and spontaneous abortion (5/0). Among these outcomes, preterm birth had moderate evidence of a positive association with phthalate exposure (specifically DEHP, DBP, and DEP). Exposure levels for BBP, DIBP, and DINP were generally lower than for the phthalates with an observed effect, which may partially explain the difference due to lower sensitivity. Other phthalate/outcome combinations were considered to have slight or indeterminate evidence of an association. Conclusions and implications of key findings: Overall, these results support that some phthalates may be associated with higher odds of preterm birth in humans, though there is some remaining inconsistency. More evidence is needed on the mechanism and relevant exposure window for this association.The views expressed are those of the authors and do not necessarily represent the views or policies of the U.S. EPA.